Alessandro Tassoni e i “Politicorum libri” di Justus Lipsius: citazione e contestazione - Enrico Zucchi (Prof. Rinaldo Rinaldi, 2021)
Even if Alessandro Tassoni fully translated Justus Lipsius’ “Politicorum libri” a few years after the publication of the princeps edition (1589), critics have frequently diminished the impact of Lipsian thought on his writings. This article aims at refuting this thesis, showing how the “Politicorum libri” permeate Tassoni’s ideas. However, the comparison with Lipsius, characterised by a strong polemical spirit, is not patent. Rather, it develops through a subtle quotation game: in his texts, Tassoni includes various references to Tacit that Lipsius had used to sustain his absolutist, hispanophile and conservative thought, reversing its sense.